Kathmandu Valley: A Living Cultural Heritage City of Nepal - Subedi, Salik Ram; Shrestha, Sudha (MAJ - Malaysia Architectural Journal, 2025)
Nepal is a country with a rich cultural legacy and diversified caste, ethnicity, language, and culture. A UNESCO World Heritage Site, the Kathmandu Valley lies at the foot of the Himalayas in Nepal. There are chariot celebrations, fairs, festivals, stone spots, art and architecture, and traditions everywhere throughout the day year in Kathmandu Valley. The Kathmandu Valley’s rich and diverse cultural legacy is reflected in the immovable and movable buildings, artwork, and festivals there. The living heritage of the Kathmandu Valley is the result of thousands of years of constant evolution and adaptation. Living heritage is an enduring custom passed down from generation to generation. For many years, the guthi system has nurtured Nepal’s physical and intangible cultural legacy via the community. The endowment property was used for religious rituals, humanitarian endeavors, and the preservation of cultural customs. This article strongly emphasizes the need for indigenous systems, traditional designs, native resources, local knowledge/skills, and traditional practices for the preservation and conservation of living cultural heritage (tangible and intangible) in place of modern technology. This article focuses on the study of tangible and intangible heritage through the case study of different valuable heritages in Kathmandu Valley. This research paper mainly concentrates on the roles and responsibilities of tangible and intangible activities for the effective conservation and management of cultural heritage in Kathmandu Valley. Similarly, developing such a strategy and mechanism focuses on the sustainability of the importance of living heritage in the Kathmandu Valley.